2017
DOI: 10.1016/j.theriogenology.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Dry ice is a reliable substrate for the distribution of frozen mouse spermatozoa: A multi-centric study

Abstract: Disseminating mouse stocks as frozen materials offers both ethical and logistical advantages over live animal shipment, minimizing the welfare issues and avoiding some of the complex custom regulations that are associated with live animal transportation. Embryo freezing in liquid nitrogen (LN) at -196 °C has traditionally been the method of choice for archiving mouse lines. However, spermatozoa freezing is emerging as a more convenient alternative due to the application of innovative cryopreservation and recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Moreover, dry ice is less costly than LN 2 . Our results strongly support that dry ice is a reliable substrate for distributing mouse sperm [6] and demonstrate that sperm frozen by the ST method are suitable for shipping in dry ice.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, dry ice is less costly than LN 2 . Our results strongly support that dry ice is a reliable substrate for distributing mouse sperm [6] and demonstrate that sperm frozen by the ST method are suitable for shipping in dry ice.…”
supporting
confidence: 79%
“…The ST method may also be applied for promoting the distribution of mouse sperm. Although a recent study reported that frozen mouse sperm can be transported in dry ice without losing fertility [6], the most common transport method currently used by the scientific community is shipment in LN 2 using dry shippers. Shipping in dry ice has several advantages compared to shipping in LN 2 : it is safer, does not require a special dry-shipper container, and can be conducted in a Styrofoam box, which does not need to be returned to the sender.…”
mentioning
confidence: 99%
“…Sperm cryopreservation is the best way to preserve mouse resource because the sperm can permanently maintain motility and fertility and applicable to IVF after thawing [ 8 ]. More than 22,000 strains of cryopreserved sperm were archived in mouse repositories, and the sperm can be transported at −196°C in dryshipper or −79°C using dry ice [ 5 , 28 , 29 ]. However, the motility of frozen–thawed mouse sperm declined compared with that of fresh sperm, and the quality of cryopreserved sperm depends on protocol, skill, and mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the transport of cryopreserved sperm and embryos could be a useful means to avoid such risks. The cryopreservation of sperm and embryos requires ultra-low temperatures using special containers (dry shippers) and proficient skills to handle the cryopreserved samples 1 , 2 . Furthermore, the use of freeze-dried sperm in the production of pups via intracytoplasmic sperm injection is associated with technical barriers 3 .…”
Section: Introductionmentioning
confidence: 99%